PENGGUNAAN MEDIA SOSIAL INSTAGRAM SCHOLARS_IG SEBAGAI MEDIA PROMOSI DIGITAL PROGRAM BEASISWA - Izzatul Chumairoh; Sandy Permata (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2021)
Social media is a platform that can influence many people. Many people use it not only as a place of remembrance that can be seen by the public but can also be used to provide information, knowledge and tucked in it for promotional media. Instagram is one of the platforms that is considered very effective in providing the latest information, almost everyone has the Instagram social media. The use of Instagram Scholars_Ig Social Media can attract followers to join the scholarship program online. The purpose of this study was to identify and explain the use of Instagram social media "Scholars_Ig" as a promotional medium for the digital scholarship program. The type of research used in this research is qualitative with case study method. The data analysis technique used is in-depth interviews from several sources and non-participant observations by visiting official intellectual companies. The results of the research obtained by researchers regarding that Scholars ig have carried out media promotions by create content marketing and online. Scholar Ig also create an event and announce to the member by direct message and online sales promotion by instagram. The Scholars_ig Instagram account is managed by a team headed by Social Media Management or what is called SMM in which there is an Instagram admin creative team.